Analisis Campur Kode Dalam Video Denny Sumargo Dan Cinta Laura (Kajian Sosiolinguistik) - Putri Mayang (Universitas Katolik Widya Karya Malang, 2023)
This study focuses on the Analysis of Code Mixing in the Video of Denny Sumargo and Cinta Laura (Sociolinguistic Studies). The purpose of this study is to describe the code mixing contained in the video. This type of research is descriptive qualitative, that is, this method simply concludes narrative words. The data collection technique is; observing videos, obtaining data by recording speech included in code mixing, identifying data, then drawing conclusions. The results of the study describe that in the video that has a duration of 31.46, the researcher only recorded 23 code mixing. Because it is clear from some of the code mixing that has been described. In the podcast video, speakers use two languages when speaking. Denny Sumargo and Cinta Laura are bilinguals, because they can use two languages in a conversation. Based on the results of the study it can be concluded that code mixing occurs in every speaker in communicating. The use of code mixing is due to the variety of languages and the bilingualism of speakers who master two languages. In the video it is clear that speakers use two languages, namely Indonesian and English when communicating.